2013
DOI: 10.1902/jop.2012.120377
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Periodontal Treatment to Improve Metabolic Control in Patients With Chronic Periodontitis and Type 2 Diabetes: A Meta‐Analysis of Randomized Clinical Trials

Abstract: The meta-analysis results seem to support the effectiveness of SRP in the improvement of glycemic control in patients with CP and DM2; however, future studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
92
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(110 citation statements)
references
References 88 publications
(238 reference statements)
10
92
0
8
Order By: Relevance
“…An improvement in the mean HbA 1 c and FPG values was demonstrated in type 2 DM patients who received non-surgical periodontal treatment. This result is consistent with the findings of earlier studies 7,16) suggesting the contribution of non-surgical periodontal therapy to glycemic control in DM patients. A reduction in HbA 1 c is important, as it is associated with a reduced risk for complications in diabetes 15) .…”
Section: Discussionsupporting
confidence: 93%
“…An improvement in the mean HbA 1 c and FPG values was demonstrated in type 2 DM patients who received non-surgical periodontal treatment. This result is consistent with the findings of earlier studies 7,16) suggesting the contribution of non-surgical periodontal therapy to glycemic control in DM patients. A reduction in HbA 1 c is important, as it is associated with a reduced risk for complications in diabetes 15) .…”
Section: Discussionsupporting
confidence: 93%
“…Scaling and root planing (SRP) is a common and non-invasive periodontal therapeutic strategy which has been reported to improve glycemic status in patients with type 2 diabetes mellitus (T2DM) [16][17][18][19][20][21]. Similar results were reported by Javed et al [8] in a patient population of prediabetic individuals.…”
Section: Introductionmentioning
confidence: 53%
“…Both the 2013 consensus report of the Joint European Federation for Periodontology and American Academy of Periodontology Dental-Medical care delivery in T2DM workshop on periodontitis and systemic diseases 13 and metaanalysis of the impact of periodontal treatment on hemoglobin A1c levels (HbA1C), 14 concluded that guideline provision surrounding periodontal care in diabetic patients was supportable and associated with efficacy, and was further supported by meta-analysis of level A clinical trial evidence demonstrating moderate reduction in HbA1c and inflammatory biomarker levels and improvement in oral indices post intervention. 15 The American Academy of Oral Medicine also advanced evidence-based CPGs that include recommendations for optimizing clinical interventions to reduce risk of PD, caries, and oral infection in patients with Glurich, Nycz, Acharya Characterize current practice patterns for integrating dental practitioners into the medical home model. Study focused on identifying best practices and education on strategic initiatives for medical-dental home set-up.…”
Section: Current Interdisciplinary Practice Patterns: Does Oral Healtmentioning
confidence: 99%